The costs and effects of workplace accidents. Twenty case studies from Ireland - Ireland. Health and Safety Authority (Dublin, 2007)
"This report presents details and analysis of twenty case studies of accidents at work. The aim of the research is to highlight for employees and employers, the financial, physical and psychological effects an accident at work can have."